2016
DOI: 10.1111/luts.12126
|View full text |Cite
|
Sign up to set email alerts
|

Urothelial Dysfunction and Chronic Inflammation in Diabetic Patients with Overactive Bladder

Abstract: Urothelial dysfunction and chronic suburothelial inflammation may contribute to the pathogeneses of OAB. However, DM does not aggravate the severity of urothelial inflammation in OAB patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(19 citation statements)
references
References 22 publications
0
19
0
Order By: Relevance
“… 16 , 17 , 35 However, little attention has been focused on the bladder, with only a single recent study drawing a correlation between inflammation, urothelial dysfunction, and diabetes in patients. 18 To our knowledge, this is the first study to directly address bladder inflammation in an animal model of diabetes, and we found direct evidence that the bladder is indeed inflamed.…”
Section: Discussionmentioning
confidence: 60%
See 1 more Smart Citation
“… 16 , 17 , 35 However, little attention has been focused on the bladder, with only a single recent study drawing a correlation between inflammation, urothelial dysfunction, and diabetes in patients. 18 To our knowledge, this is the first study to directly address bladder inflammation in an animal model of diabetes, and we found direct evidence that the bladder is indeed inflamed.…”
Section: Discussionmentioning
confidence: 60%
“… 13 15 While for many years there has been general evidence that inflammation plays an important role in the development of several diabetic complications, 16 , 17 there has been little evidence that it is occurring in the bladder. Suggestive indications were provided when Wang and Kuo 18 recently found that mast cells in the urothelium and suburothelial layer were increased in diabetic patients. In this study, we have examined the presence of inflammation in the bladder of the Akita diabetic mice at a time where they demonstrate DBD symptoms.…”
Section: Introductionmentioning
confidence: 99%
“…Previous reports have demonstrated that OAB may be caused by chronic inflammation (51,52) and proteins related with inflammation can be served as biomarker for OAB syndrome (53). In addition, modulating inflammatory response with anti-inflammation drugs can improve the detrusor contraction disorder (54,55).…”
Section: Discussionmentioning
confidence: 99%
“…[44] These animal and clinical studies of BoNT-A strengthen the evidence of its therapeutic effects in diabetic patients with OAB. Since muscarinic M3 and P2X3 protein expressions in the bladders of DM-associated OAB patients were significantly higher than those in the controls, BoNT-A detrusor injection may provide an alternative treatment for these patients [23].…”
Section: Inhibition Of Chronic Inflammation and Hypersensitivity By Imentioning
confidence: 96%
“…The findings of the animal studies have been further corroborated by a human study. Bladder mucosa was biopsied from 19 DM-associated OAB patients, 14 OAB patients without DM, and 10 healthy controls [23]. Decreased expression of urothelial junction protein (E-cadherin and ZO-1) and increased urothelial inflammation (mast cells) were noted in the non-diabetic OAB and diabetic OAB patients.…”
Section: Pathophysiology Of Dm-associated Oabmentioning
confidence: 99%